PERBAIKAN GENETIK ANGGREK MELALUI PERSILANGAN INTERGENERIK DAN PERBANYAKAN SECARA IN VITRO DALAM MENDUKUNG PERKEMBANGAN ANGGREK DI INDONESIA - DWI SUSILO UTAMI; SRI HARTATI (Fakultas Pertanian, Universitas Tunas Pembangunan Surakarta, 2012)
The research aimed to get the most suitable media and foliar fertilizer to acclimate plantlet of orchid hybrid resulted from inter generic crossing of Phalaenopsis sp vs Vanda tricolor and to study the difference of the chromosomal structure compared to their parents. The research showed that the best growing media for hybrid seeds of ♀ Vanda tricolor x ♂Phalaenopsis Pinlong Cinderella was pakis, the most suitable fertilizer was Hyponex 2g/l, number of parental chromosomes of Vanda tricolor 2n = 38, while Phalaenopsis pinlongcinderela; Phalaenopsis Joane Killeup June; the hybrid of ♀ Vanda tricolor x ♂ Phalaenopsis joankileup june) and the hybrid of ♀Vanda tricolorx ♂Phalaenopsis Pinlong Cinderella had the same chromosomes, 2n = 40. The chromosome size of V. tricolor ranged (1,94 ± 0,16) µm to (4,72 ± 0,19) µm, while Phalaenopsis Joane Killep June ranged (0,84 ± 0,02) µm to (2,97 ± 0,13) µm, Phalaenopsis pinlong cinderela was from (2,02 ± 0,15) µm hingga(5,91 ± 0,78) µm, the hybrid of ♀Vanda tricolor dengan ♂ Phalaenopsis joankileup june.) was from (1,77 ± 0,20) hingga (1,69 ± 0,24) µm, the hybrid of ♀Vanda tricolor dengan ♂ Phalaenopsis pinlong cinderela)was from (1,86 ± 0,03) µm to (6,74 ± 0,59) µm. The caryotype arrange-ment was also different. Vanda. tricolor 2n = 18 m + 1 sm, Phalaenopsis joankileup June 2n=13 m+7 sm., Phalaenopsis pinlong cinderela 2n = 18 m + 2 sm, while the hybrid of ♀Vanda tricolor x ♂ Phalaenopsis Joankileup june.) and the hybrid of ♀Vanda tricolor dengan ♂ Phalaenopsis pinlong cinderela) had the same karyotype, 2n = 17 m + 3 sm.